2022
DOI: 10.1101/2022.01.24.22269786
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Who Develops Pandemic Fatigue?

Abstract: According to the World Health Organization, pandemic fatigue poses a serious threat for managing COVID-19. The cardinal feature of pandemic fatigue is a progressive decline in adherence to social distancing (SDIS) guidelines, which is associated with pandemic-related emotional burnout. Little is known about the nature of pandemic fatigue; for example, it is unclear who is most likely to develop pandemic fatigue. We sought to evaluate this issue based on data from 5,812 American and Canadian adults recruited du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Table 1, however, is not all-encompassing, and researchers and practitioners may want to consider newly emerging conceptualizations of pandemic-related distress. For example, given how long COVID-19 has lasted, OHP researchers and practitioners may be interested in assessing workers' pandemic fatigue and apathy (see, e.g., Lilleholt et al, 2022;Taylor et al, 2022). These manifestations of COVID-19 distress may have unique implications for occupational safety and disease spread in the workplace.…”
Section: Covid-19 Distress Measure Mattersmentioning
confidence: 99%
“…Table 1, however, is not all-encompassing, and researchers and practitioners may want to consider newly emerging conceptualizations of pandemic-related distress. For example, given how long COVID-19 has lasted, OHP researchers and practitioners may be interested in assessing workers' pandemic fatigue and apathy (see, e.g., Lilleholt et al, 2022;Taylor et al, 2022). These manifestations of COVID-19 distress may have unique implications for occupational safety and disease spread in the workplace.…”
Section: Covid-19 Distress Measure Mattersmentioning
confidence: 99%
“…One source of bias emerges from the possibility of confounding due to omitted variables (i.e., alternative explanations). Many of the relevant omitted variables are stable individual-level characteristics such as chronic mental challenges, general health concerns, general political trust, or a lack of socioeconomic opportunities ( 7 , 29 ). If such factors simultaneously exert independent impacts on pandemic fatigue and political discontent, then they create omitted variable bias in the estimates.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, to assess the convergent validity of the present measure with other measures of pandemic fatigue, a separate study was conducted in Germany in March 2022 ( 40 ). In this study, we assessed pandemic fatigue using the present measure as well as a validated pandemic fatigue scale ( 7 ) and a validated scale for “COVID-19 burnout” ( 29 ). In support of the measure’s convergent validity, we found large correlations between our item and the pandemic fatigue scale (r = 0.48), and particularly with its behavioral fatigue subcomponent (r = 0.52), and a lower, albeit still sizable correlation with the COVID-19 burnout scale (r = 0.30) ( SI Appendix , section S1.5 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has indicated that COVID-19 pandemic has amplified stress of a significant proportion of population (Panchal et al, 2021;Prati & Mancini, 2021). Excessive stress can notably lead to burnout, a prominent factor in pandemic fatigue (Marčinko et al, 2020;Taylor et al, 2022;Yildirim & Solmaz, 2020). Burnout is a psychological construct defined by the experience of emotional exhaustion, reduced personal accomplishment/inefficacy, and depersonalization/cynicism (Maslach & Jackson, 1981;Maslach & Leiter, 2016).…”
Section: Mitigating Burnout and Using Adaptive Distractionsmentioning
confidence: 99%